Cognition of Foucault; A Practice That Must be Ridded A Critical Review on the Book "Foucault in Iran")Foucault in Iran: Islamic Revolution after the Enlightenment( - Meisam Ghahreman (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Foucault's view of the Islamic Revolution, both during his lifetime and after, provoked different debates and reactions and various works were written about it. One of the most controversial works is “Foucault and the Iranian Revolution: Gender and the Seductions of Islamism” by Janet Afary and Kevin B. Anderson. On the one hand, this book can be considered a political reaction to Islamism, and on the other hand, it is an epistemological critique of what the authors call "cultural relativism". Behrooz Ghamari-Tabrizi in his book "Foucault in Iran" while presenting the truth of Foucault's views on the Iranian revolution, also gives an appropriate answer to Afary and Anderson. In other words, in this book, he seeks to answer the question: How did Foucault make sense of the Iranian revolution? The present article has examined this issue from a particular point of view both of these works are formed within a discourse practice and, therefore, are different sentences of a statement and we must get rid of both equally.